Optimization of transparent conducting oxides in heterojunction solar cells by excimer laser annealing. (Optimización de óxidos conductores transparentes en las células solares de heterounión mediante recocido láser excimer) - Alleman V. (2015)
One of the most important problems in our society is the lack of clean energy sources to overcome the energetic crisis and global warming. For this reason, I enrolled “Master en Energías Renovables y Eficiencia Energética” at UNI. This master gave me a good training and knowledge to face real problems concerning renewable energies. I chose photovoltaic solar energy because my major interest in physics are solid state physics and material science, in this manner I could bring together my two passions for material science and green energy.